2022
DOI: 10.1093/beheco/arac012
|View full text |Cite
|
Sign up to set email alerts
|

Should I stay or should I go? Behavioral adjustments of fur seals related to foraging success

Abstract: Understanding foraging strategies and decision-making processes of predators provide crucial insights into how they might respond to changes in prey availability and in their environment to maximize their net energy input. In this work, foraging strategies of Antarctic fur seals (Arctocephalus gazella, AFS) and Northern fur seals (Callorhinus ursinus, NFS) were studied to determine how they adjust their foraging behavior according to their past prey capture experiences. AFS on Kerguelen Islands are exclusively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…While we cannot test this hypothesis, we were able to study the fine‐scale hunting behavior of AFS to infer information on prey behavior. In particular, a previous study using sonar and movement tags showed that evasive prey were associated with higher swimming efforts and longer prey capture events (Chevallay et al, 2023). Here we compared these two behavioral parameters between the female that consistently produced calls (ind.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While we cannot test this hypothesis, we were able to study the fine‐scale hunting behavior of AFS to infer information on prey behavior. In particular, a previous study using sonar and movement tags showed that evasive prey were associated with higher swimming efforts and longer prey capture events (Chevallay et al, 2023). Here we compared these two behavioral parameters between the female that consistently produced calls (ind.…”
Section: Discussionmentioning
confidence: 99%
“…Prey capture attempts (PrCAs hereafter) were detected from the 250 Hz tri‐axial acceleration data recorded by tags, by computing the norm of the differential of the tri‐axial acceleration (norm‐jerk hereafter), as described in (Chevallay et al, 2023). Spikes in the norm‐jerk signal higher than 3,000 m/s 2 were classified as prey strikes (Chevallay et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These plots showed a bimodal distribution with a minimum at 3000 m.s -2 for all individuals, and was set as a threshold to identify strikes in the full norm-jerk series. As prey may be encountered in patches or may elude capture, leading to a bout structure in prey strikes, strikes occurring less than 15 s from the previous strike were grouped in the same PrCA bout (referred as bout hereafter) according to the distribution of inter-strike interval (Chevallay et al, in revision).…”
Section: Methodsmentioning
confidence: 99%